Rationality and Utility of Evaluation Reseach in Policy Making - Lake, Anda (2011)
Abstract: "In this article, the author explores the issues associated with the practical significance of evaluation research in the policy making environment of Latvia. Sporadic, selective and rare use of the results of evaluation research is viewed as the central issue of the paper. The objective of this article is to reveal the connection between the action strategy of the groups involved in the implementation of evaluation research and manifestations of practical significance of evaluation. Implementation, utilisation and practical importance of evaluation research are examined not only in relation to rational action strategies of the groups, but also in relation to the understanding of the concept of practical significance of evaluation research. The theoretical framework of the article is based on the conceptual understanding of J. Habermas’ purposive rationality and communicative rationality, as well as C. H. Weiss’ understanding of practical utilisation of evaluation (the instrumental